Deciphering Patterns of Scammed Messages Using SFL’s Interpersonal and Experiential Metafunctions - PABLO, ELEN (International Journal of Language and Literary Studies, 2025)
This study explores the linguistic patterns employed in online scam communications by investigating the conversation between a scammer and their target through the lens of Systemic Functional Linguistics. The objectives of the study were: 1) to determine the function of the transitivity processes and participant involvement in conveying intended messages 2) analyze mood choices to understand interaction dynamics and role construction. This exploration adopted the qualitative approach focusing on transitivity processes and mood choices. The findings reveal that scammers manipulate conversations through strategic use of transitivity processes, employing material and relational processes to assert dominance and position the target as submissive and compliant; they strengthen power dynamics through mood choices, mainly using declarative moods to establish authority while the target’s interrogative moods emphasize their subordinate role. The study recommends that interdisciplinary approaches that investigates the psychological impact of linguistic manipulation on targets be conducted to prevent scam effectively.